Climate Consciousness vs. Profit Chase : Asset Behavior in a Sustainable Era - Singh, Amit Kumar; Jain, Srishti; Goel, Rashmi (Indian Journal of Finance, 2026)
Purpose : The present study aimed to find a solution to the sustainability dilemma between conventional and digital assets. Design : The study employed two conventional assets/commodities, i.e., gold, oil & gas, and three digital assets, i.e., Bitcoin, Ethereum, and DeFi, from 2017 to 2024 on a daily basis. The financial price data representing the underlying investor sentiments was extracted from S&P for all the variables. A structural break was considered, focusing on the major algorithm alteration for Ethereum in 2022. Therefore, Autoregressive Distributed Lag (ARDL) models have been employed for two different time frames. Findings : The results suggested that conventional assets had a positive and significant relation with sustainability, proxied by Environment, Social, and Governance (ESG). In contrast, digital assets like Bitcoin and Ethereum do not hold a significant relation. To our surprise, the coefficient turned negative for Bitcoin and Ethereum after the structural change. Therefore, the findings revealed that crypto investors are least bothered about climatic conditions and are gung-ho for earning huge returns. Practical Implications : It is recommended to initiate a green framework for digital assets. Additionally, ESG disclosures help sensitized investors to climate change. Originality : Prior literature lacks a comprehensive comparative analysis of the conventional and digital assets in the context of sustainability.